2009
DOI: 10.17221/1642-pse
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater efficient use of the cellar-greenhouse system on slope land in hilly semi-arid area of North China

et al.

Abstract: Water resources in semi-arid and arid regions are the most strongly limiting factor of the growth for plants. Rainwater efficient use is one of the focuses of the water resources research. In this paper, an experiment was conducted at Ka Zuo Research Station of Ecological Agriculture, Institute of Applied Ecology, Chinese Academy of Sciences in the hilly semi-arid area of North China. It aimed at studying the efficient use of rainwater harvesting of the cellargreenhouse system (CGS). Results showed that, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Moreover, it performs important regulatory functions for soil water, fertilizers, gases, heat and biological activity [27]. Compared with furrow irrigation, the soil bulk density and soil porosity of SUI in solar greenhouses were 21.2% lower and 29.0% higher, respectively [28,29]. In our study, the soil bulk density of SUI was significantly lower than that of FLI, and the total soil porosity, capillary porosity and non-capillary porosity of SUI were all significantly higher than those of FLI, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it performs important regulatory functions for soil water, fertilizers, gases, heat and biological activity [27]. Compared with furrow irrigation, the soil bulk density and soil porosity of SUI in solar greenhouses were 21.2% lower and 29.0% higher, respectively [28,29]. In our study, the soil bulk density of SUI was significantly lower than that of FLI, and the total soil porosity, capillary porosity and non-capillary porosity of SUI were all significantly higher than those of FLI, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies on soil water movement and water use efficiency using SUI for vegetable production in solar greenhouses or in the field have been reported [27,28,32]. However, few studies have focused on soil water movement and water use efficiency when using SUI in orchards.…”
Section: Discussionmentioning
confidence: 99%
“…Water resources in semi-arid and arid regions are the most important limiting factors of plant growth. Therefore, effective use of rainwater is one of the focal points of research carried out on water resources (Gao et al, 2009). The rainwater on greenhouse roof can be used to irrigate plants grown in the greenhouses if properly harvested and stored.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al (2009) examined soil erosion under different land uses and land-use combinations and found that land under mature forests had the lowest erosion rates while terraced cropland produced the highest rates. On the other hand, slope gradient is an important factor affecting erosion and often has an impact on the human choice of land use (Fu et al 2006;Gao et al 2009). Therefore, the study of land use change and the distribution of land use types according to slope gradient are important for soil and water conservation on the Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%